2003
DOI: 10.1659/0276-4741(2003)023[0378:ciatra]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

CDE's Integrative Approach to Research and Development in Mountain Regions

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…At the level of research centers and programs, several articles reported on factors that facilitated inter-and transdisciplinarity: multi-stakeholder partnerships combining research, planning, and decision-making for sustainable development (Hurni et al 2003;Liechti 2014); seminar series for academics and stakeholders (Bergier 2006;Roux et al 2018); joint books on a common research topic allowing the reinterpretation of disciplinary knowledge (Attali et al 2014); the use of graphic time lines as ''boundary objects'' that could facilitate dialogue between disciplines (Bergeret et al 2015); the availability of ''contingency funds'' to adjust to emerging ideas (Mitchell et al 2017); and international cooperation in more or less formal agreements, such as the Mountain Partnership and the Alpine and Carpathian conventions (Ross 2006;Veit and Scheurer 2006;Messerli 2012;Scheurer et al 2013).…”
Section: Inter-and Transdisciplinarity In Mountain Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of research centers and programs, several articles reported on factors that facilitated inter-and transdisciplinarity: multi-stakeholder partnerships combining research, planning, and decision-making for sustainable development (Hurni et al 2003;Liechti 2014); seminar series for academics and stakeholders (Bergier 2006;Roux et al 2018); joint books on a common research topic allowing the reinterpretation of disciplinary knowledge (Attali et al 2014); the use of graphic time lines as ''boundary objects'' that could facilitate dialogue between disciplines (Bergeret et al 2015); the availability of ''contingency funds'' to adjust to emerging ideas (Mitchell et al 2017); and international cooperation in more or less formal agreements, such as the Mountain Partnership and the Alpine and Carpathian conventions (Ross 2006;Veit and Scheurer 2006;Messerli 2012;Scheurer et al 2013).…”
Section: Inter-and Transdisciplinarity In Mountain Researchmentioning
confidence: 99%
“…Since then, numerous research centers and programs on mountains have been created. Many of them have a strong emphasis on integrating different scientific disciplines and nonacademic stakeholders for sustainable development (Hurni et al 2003;Glass et al 2013;Attali et al 2014;Liechti 2014;Roux et al 2018;Reynard et al 2020). The organization of frequent international conferences and the creation of peer-reviewed journals like Mountain Research and Development were likewise aimed at supporting inter-and transdisciplinary research to promote the sustainability of mountain regions.…”
Section: Introductionmentioning
confidence: 99%